Comparative study of porphyrin derivatives in monolayers at the air-water interface and in langmuir-blodgett films - Ghosh, Amrita; Mahato, Prasenjit; Choudhury, Sipra; Das, Amitava (Thin Solid Films, 2011)
The orientation and aggregation of various porphyrin derivatives at the air–water interface and in Langmuir–Blodgett films were investigated. Monolayer properties of these molecules, where long alkyl chain(s) were covalently bound through different functionality of varying hydrophilicity were studied by measuring surface pressure area isotherms. Such derivatives, where ether functionality (functionalities) was (were) used for linking long alkyl chain(s), did not form uniform monolayer; instead they were found to form multilayer clusters or aggregates on the water surface. On the other hand, porphyrin derivative functionalized at the four peripheral phenyl rings with eight hexadecyl ether chains formed stable spherical vesicles when deposited on mica. Tetra N-alkyl pyridinium porphyrins with long alkyl chain were found to form various phases on the water surface. Evidence of transition from horizontal orientation to vertical orientation of porphyrin rings of porphyrin molecules having C14 chains was observed. This type of transition was lost with the porphyrin molecule with a relatively smaller chain (C8).

Diamine derivative of a ruthenium(II)-polypyridyl complex for chemodosimetric detection of nitrite ion in aqueous solution - Ghosh, Amrita; Das, Priyadip; Saha, Sukdeb; Banerjee, Tanmay; Bhatt, Harshad B.; Das, Amitava (Inorganica Chimica Acta, 2011)
Nitrite is quite an abundant anion in the environment. It, however, becomes toxic to human life, as well as aquatic animals when present above the permissible concentration level. We have reported here a Ru(II)-polypyridyl-based complex (1) for chemodosimetric detection of nitrite ion in aqueous solution. Formation of the new triazole based complex, generated by reaction of 1 and N2O3, is ascertained by comparing its properties with a presynthesised triazole complex.

Exciton-coupled charge-transfer dynamics in a porphyrin J-aggregate/TiO 2 complex - Verma, Sandeep; Ghosh, Amrita; Das, Amitava; Ghosh, Hirendra Nath (Chemistry a European Journal, 2011)
Exciton-coupled charge-transfer (CT) dynamics in TiO2 nanoparticles (NP) sensitized with porphyrin J-aggregates has been studied by femtosecond time-resolved transient absorption spectroscopy. J-aggregates of 5,10,15-triphenyl-20-(3,4-dihydroxyphenyl) porphyrin (TPPcat) form CT complexes on TiO2 NP surfaces. Catechol-mediated strong CT coupling between J-aggregate and TiO2 NP facilitates interfacial exciton dissociation for electron injection into the conduction band of the TiO2 nanoparticle in pulse width limited time (<80 fs). Here, the electron-transfer (<80 fs) process dominates over the intrinsic exciton-relaxation process (J-aggregates: ca. 200 fs) on account of exciton-coupled CT interaction. The parent hole on J-aggregates is delocalized through J-aggregate excitonic coherence. As a result, holes immobilized on J-aggregates are spatially less accessible to electrons injected into TiO2, and thus the back electron transfer (BET) process is slower than that of the monomer/TiO2 system. The J-aggregate/porphyrin system shows exciton spectral and temporal properties for better charge separation in strongly coupled composite systems.

Photoactive RuII-polypyridyl complexes that display sequence selectivity and high-affinity binding to duplex DNA through groove binding - Ghosh, Amrita; Das, Priyadip; Gill, Martin R.; Kar, Prasenjit; Walkar, Michael G.; Thomas, Jim A.; Das, Amitava (Chemistry A European Journal, 2011)
The duplex-DNA binding properties of a nonintercalating polypyridyl ruthenium(II) complex that incorporates a linear extended ligand with a catechol moiety has been probed with a variety of photo- and biophysical techniques. These studies reveal that the complex groove binds to DNA sequences biphasically, and displays binding constants equivalent to those of high-affinity metallointercalators. The complex also displays preferential binding to AT-rich sequences. Changes in the structure of the coordinated catechol ligand and the incorporation of intercalating ancillary ligands into the complex were found to modulate both the optical-binding response and binding parameters of the system, which indicates that the catechol moiety plays a crucial role in the observed enhancement to binding affinities.

Urea/thiourea derivatives and Zn(II)-DPA complex as receptors for anionic recognition-a brief account - Das, Priyadip; Mahato, Prasenjit; Ghosh, Amrita; Mandal, Amal Kumar; Banerjee, Tanmay; Saha, Sukdeb; Das, Amitava (Journal of Chemical Sciences, 2011)
This review covers few examples of anion complexation chemistry, with a special focus on urea/thiourea-based receptors and Zn(II)-dipicolyl amine-based receptors. This article specially focuses on structural aspects of the receptors and the anions for obtaining the desire specificity along with an efficient receptor–anion interaction. Two types of receptors have been described in this brief account; first one being the strong hydrogen bond donor urea/thiourea derivatives, which binds the anionic analytes through hydrogen bonded interactions; while, the second type of receptors are coordination complexes, where the coordination of the anion to the metal centre. In both the cases the anion binding modulate the energy gap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) and thereby the spectroscopic response. Appropriate choice of the signalling unit may allow probing the anion binding phenomena through visual detection.

ZnII-2,2?:6?,2?-terpyridine-based complex as fluorescent chemosensor for PPi, AMP and ADP - Das, Priyadip; Ghosh, Amrita; Kesharwani, Manoj K.; Ramu, Vadde; Ganguly, Bishwajit; Das, Amitava (Europian Journal of Inorganic Chemistry, 2011)
A new ZnII–2,2′:6′,2″-terpyridine complex, derivatized with a coumarin moiety (L1Zn), acts as a fluorescent chemosensor for different biologically important phosphates like PPi, AMP and ADP in mixed aqueous media. Depending on the proportion of the aqueous fraction present in the solvent mixture, L1Zn shows a preference for different phosphate moieties at physiological pH. In an aqueous acetonitrile (2:3, v/v) medium this reagent shows a preference for AMP as compared to ADP, ATP and PPi. The binding affinities of L1Zn with different phosphate ions and associated shifts in the electronic spectra were rationalized by DFT calculations. Such an example of a receptor that is selective for AMP under physiological conditions is rare in the literature.

Zn(II)-cyclam based chromogenic sensors for recognition of atp in aqueous solution under physiological conditions and their application as viable staining agents for microorganism - Mahato, Prasenjit; Ghosh, Amrita; Mishra, Sanjiv K.; Shrivastav, Anupama; Mishra, Sandhya; Das, Amitava (Inorganic Chemistry, 2011)
Two chromogenic complexes, L.Zn (where L is (E)-4-((4-(1,4,8,11-tetraazacyclotetradecan-1-ylsulfonyl)phenyl)diazenyl)-N,N-dimethylaniline) and its [2]pseudorotaxane form (α-CD.L.Zn), were found to bind preferentially to adenosine triphosphate (ATP), among all other common anions and biologically important phosphate (AMP, ADP, pyrophosphate, and phosphate) ions in aqueous HEPES buffer medium of pH 7.2. Studies with live cell cultures of prokaryotic microbes revealed that binding of these two reagents to intercellular ATP, produced in situ, could be used in delineating the Gram-positive and the Gram-negative bacteria. More importantly, these dyes were found to be nontoxic to living microbes (eukaryotes and prokaryotes) and could be used for studying the cell growth dynamics. Binding to these two viable staining agents to intercellular ATP was also confirmed by spectroscopic studies on cell growth in the presence of different respiratory inhibitors that influence the intercellular ATP generation.

Highly selective and dual responsive test paper sensor of Hg2+/ Cr3+ for naked eye detection in neutral water - Das, Priyadip; Ghosh, Amrita; Bhatt, Hitesh; Das, Amitava (RSC Advances, 2012)
A highly selective and sensitive colorimetric and fluorogenic sensor (L1) for Hg2+/Cr3+ is reported. This reagent (L1) was synthesized by reacting 4-((4 (dimethylamino)phenyl)diazenyl)benzene-1-sulfonyl chloride, which has a dimethylaminophenyldiazenyl fragment as a photoactive signalling unit, with 2,2′-(3,3′-azanediylbis(propane-3,1-diyl))diisoindoline-1,3-dione as the receptor fragment. The reagent was characterized by standard analytical and spectroscopic techniques. Electronic spectral studies revealed that the reagent was selective for Hg2+ and Cr3+ in the presence of all other metal ions of Group 1A, IIA and all other common transition metal ions. On binding of L1 to the Hg2+ or Cr3+ centres, a new intense absorption band with a λmax of 509 nm appeared with associated changes in the visually detectable solution colour from yellow to red. Fluorescence spectral studies revealed a significant enhancement in the emission intensities upon coordination to Hg2+ or Cr3+ without any change in the emission wavelength. This could be explained by the efficient interruption of the photo induced electron transfer signalling mechanism involving an unshared pair of electrons from the central tertiary amine centre. An easy to prepare paper test kit, which was obtained by soaking the filter paper in a dichloromethane solution of L1, presents an approach that could be successfully used in the detection of Hg2+ or Cr3+ ions present in neutral aqueous media. This indicates the potential application of this dip strip type sensor for the detection of Hg2+ and Cr3+ in neutral aqueous environments without any spectroscopic instrumentation. Importantly, this reagent binds specifically to Cr3+ in the presence of an excess of iodide ions, which act as a masking agent for Hg2+. To the best of our knowledge, there are very few examples of detection limits lower than the present test strip for Hg2+ in the literature, while, for Cr3+, no such report is available.

Investigation of the captopril-insulin interaction by mass spectrometry and computational approaches reveals that captopril induces structural changes in insulin - Ghosh, Amrita; Pawar, Aiswarya B.; Chirmade, Tejas; Jathar, Swaraj M.; Bhambure, Rahul; Sengupta, Durba; Giri, Ashok P.; Kulkarni, Mahesh J. (ACS Omega, 2022)
ABSTRACT: Post-translational modifications remarkably regulate proteins' biological function. Small molecules such as reactive thiols, metabolites, and drugs may covalently modify the proteins and cause structural changes. This study reports the covalent modification and noncovalent interaction of insulin and captopril, an FDA-approved antihypertensive drug, through mass spectrometric and computation-based approaches. Mass spectrometric analysis shows that captopril modifies intact insulin, reduces it into its ``A'' and ``B'' chains, and covalently modifies them by forming adducts. Since captopril has a reactive thiol group, it might reduce the insulin dimer or modify it by reacting with cysteine residues. This was proven with dithiothreitol treatment, which reduced the abundance of captopril adducts of insulin A and B chains and intact Insulin. Liquid chromatography tandem mass spectrometric analysis identified the modification of a total of four cysteine residues, two in each of the A and B chains of insulin. These modifications were identified to be Cys6 and Cys7 of the A chain and Cys7 and Cys19 of the B chain. Mass spectrometric analysis indicated that captopril may simultaneously modify the cysteine residues of intact insulin or its subunits A and B chains. Biophysical studies involving light scattering and thioflavin T assay suggested that the binding of captopril to the protein leads to the formation of aggregates. Docking and molecular dynamics studies provided insights into the noncovalent interactions and associated structural changes in insulin. This work is a maiden attempt to understand the detailed molecular interactions between captopril and insulin. These findings suggest that further investigations are required to understand the long-term effect of drugs like captopril.

Multi-dimensional impact of captopril modification on human serum albumin - Ghosh, Amrita; Jani, Vinod; Sonavane, Uddhavesh; Naphade, Anvi N.; Joshi, Rajendra; Kulkarni, Mahesh J.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2024)
Captopril is a thiol drug, widely used for the management of hypertension and cardiovascular diseases. Reactive thiols are found to covalently modify the cysteines of plasma proteins and affect their structure and function. Human serum albumin (HSA) is prone to undergo modification by various low molecular weight compounds, including drugs. Cysteine34 (Cys34) in HSA has a free thiol group with antioxidant properties, considered to be the most redox-sensitive amino acid in plasma. Through mass-spectrometric analysis, we demonstrate for the first time that captopril forms a disulfide adduct at Cys34 residue and increases the protease susceptibility of HSA to trypsin. As evidenced by our biophysical and electron microscopy studies, HSA undergoes structural alteration, aggregation and morphological changes when treated with different captopril concentrations. Molecular dynamics studies further revealed the regions of secondary structural changes in HSA due to disulfide adduct formation by captopril at Cys34. It also elucidated the residues involved in the noncovalent interactions with captopril. It is envisaged that structural change in HSA may influence the efficacy of drug delivery as well as its own biological function. These findings may thus provide significant insights into the field of pharmacology intriguing further investigation into the effects of long-term captopril treatment.
Keywords: Captopril; Electron microscopy; Human serum albumin; Mass spectrometry; Molecular dynamic simulation; Spectrophotometry